The Concept of Rwa Bhineda on Investment Interest in Green Sukuk by Considering Environmental Awareness - Dewi, Ni Nyoman Sri Rahayu Trisna; Prihantari, Gusti Ayu Putu Eka Dewi (E-Jurnal Akuntansi, 2024)
Green sukuk is a sharia-based financial instrument used by the government to finance green projects. The number of green sukuk investors has continuously increased since the beginning of the green sukuk issuance, in 2019.  This is inseparable from the attractive profit sharing and very low risk. In the Hindu concept, the term Rwa Bhineda is known, which emphasises the existence of two things that are contradictory but always side by side, as is the case with profit sharing and risk in green sukuk. This research aims to examine the effect of profit sharing and risk partially on investment interest in green sukuk and examine the moderating effect of environmental awareness. The population used is all green sukuk investors with a sample size of 100 green sukuk investors. The data collection method uses a questionnaire. The data analysis technique used is Structural Equation Modeling with Partial Least Squares (SEM PLS). The results showed that profit sharing and environmental awareness has a positive and significant effect on green sukuk investment interest, risk has no effect on investment interest, environmental awareness weakens the effect of profit sharing on investment interest in green sukuk with negative direction but environmental awareness is not able to moderate the effect of risk on investment interest in green sukuk. This research combines the concept of sharia in Islam and the concept of rwa bhineda in Hinduism, making it interesting to do research.